(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article, which has scientific, theoretical and practical significance, is intended for school principals and managers working in the education system who are improving their professional skills. The methodological mechanisms provided can be used to educate students in the spirit of loyalty to the homeland based on national values, in institutions of the continuing education system, in organizing spiritual and educational events, and in additional work with students and teachers.